Phenomena of Students Anxiety in English Speaking Activities - Rika Budiarti; Dumaris E. Silalahi (Jurnal Multidisiplin Sahombu, 2025)
Speaking is one of the most important skills in English learning because it allows students to communicate ideas directly. However, many learners face speaking anxiety which makes them nervous, less confident, and unable to perform well in class. Most previous studies discussed this problem with quantitative methods, but there is still a need for a deeper description by reviewing and comparing qualitative findings. Therefore, this mini research was conducted as a descriptive qualitative library study by analyzing five previous articles related to students’ speaking anxiety. Referring to Horwitz (1986), speaking anxiety can be divided into communication apprehension, test anxiety, and fear of negative evaluation. The review shows that the dominant indicators are fear of making mistakes, lack of vocabulary, and low self-confidence. These factors cause nervousness, forgetting words, avoiding participation, and only fair scores in speaking assessments. In conclusion, speaking anxiety is a common phenomenon in English classrooms, and teachers need to provide motivation, supportive learning environments, and more speaking practice to help students reduce their anxiety and improve their performance.